Stella & Marigold - Barrows, Annie; Blackall, Sophie (San Francisco, 2024)
Two sisters, Stella and Marigold, do all the regular things, like go to school, but they also share adventures (both real and imagined) and secret sister things.
Junior Library Guild
Ages 7-9.
Grades 2-4.
A Junior Library Guild selection (JLG)
Keywords: Imagination; Fiction; Imagination; Sisters; Fiction; Family life; Fiction; Fiction; Family life; Fiction; Fiction; Juvenile fiction; Sisters; Juvenile fiction; Imagination; Juvenile fiction; Families; Sisters; Juvenile fiction